Feasibility Studies of Treated Used Cooking Palm Oil as Precursor for Bio-Lubricant - Muhamad Azwar, Azhari; Nor Hasrul Akhmal, Ngadiman; Noordin, Mohd Yusof; Ani, Idris; Norazlianie, Sazali (Semarak Ilmu Publishing, 2023)
The non-renewability and and non-biodegradability of petroleum based lubricants as well as the environmental impacts their waste contributes to the environment has caused the search for a substitute for precursor of lubricant formulation. The food security issue has caused major concerns on how vegetable oil could replace petroleum based product lubricants. This paper reports the feasibility studies of kinematic viscosity, friction and wear properties of treated used cooking palm oil as precursor for development of new bio-lubricant. The treated used cooking palm oil displayed a comparable value of kinematic viscosity of 43.6cSt, coefficient of friction of 0.126 and 122µm which is almost similar to the value of fresh cooking palm oil. Treated used cooking palm oil is seen to be a suitable candidate for precursor of bio-lubricant formulation, However, some additives may need to be added as to increase the tribological properties for treated used cooking oil to be used as a bio-lubricant.